2014
DOI: 10.1096/fj.14-262246
|View full text |Cite
|
Sign up to set email alerts
|

TAS2R bitter taste receptors regulate thyroid function

Abstract: Dysregulation of thyroid hormones triiodothyronine and thyroxine (T3/T4) can impact metabolism, body composition, and development. Thus, it is critical to identify novel mechanisms that impact T3/T4 production. We found that type 2 taste receptors (TAS2Rs), which are activated by bitter-tasting compounds such as those found in many foods and pharmaceuticals, negatively regulate thyroid-stimulating hormone (TSH)-dependent Ca(2+) increases and TSH-dependent iodide efflux in thyrocytes. Immunohistochemical Tas2r-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
102
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(104 citation statements)
references
References 57 publications
2
102
0
Order By: Relevance
“…The epithelial cells were shown to respond to PTC and also quarumsensing molecules like N-butyryl-l-homoserine lactone differentially according to the TAS2R38 genotypes so that the susceptibility to bacterial infection is maximal for AVI/AVI cells but minimal for PAV/PAV cells. Clark et al showed that human thyroid follicular cells also express TAS2R38 and other TAS2Rs and that the iodide efflux from the cells is suppressed by various bitter TAS2R ligands dose-dependently (15). Interestingly, the response was absent for a TAS2R38 agonist, PROP, in the cells derived from AVI/AVI carriers, suggesting that thyroid hormone is down-regulated by TAS2R38 and other TAS2R signaling in the thyroid follicular cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The epithelial cells were shown to respond to PTC and also quarumsensing molecules like N-butyryl-l-homoserine lactone differentially according to the TAS2R38 genotypes so that the susceptibility to bacterial infection is maximal for AVI/AVI cells but minimal for PAV/PAV cells. Clark et al showed that human thyroid follicular cells also express TAS2R38 and other TAS2Rs and that the iodide efflux from the cells is suppressed by various bitter TAS2R ligands dose-dependently (15). Interestingly, the response was absent for a TAS2R38 agonist, PROP, in the cells derived from AVI/AVI carriers, suggesting that thyroid hormone is down-regulated by TAS2R38 and other TAS2R signaling in the thyroid follicular cells.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, TAS2Rs belong to a family of 25 functional members that are clustered on chromosomes 5, 7, and 12 (1,4). TAS2Rs are expressed in various organs, including the gustatory organs, gastrointestinal tract, thyroid gland, respiratory organs, kidney, central nervous system, skin, and reproductive organs (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Many genetic polymorphisms have been identified for TAS2Rs, some of which are known to cause functional changes in bitter-taste sensitivity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In light of findings showing that Tas2r are present in organs that are not at all or only partially accessible to xenobiotics, such as brain (86 -89), testes (61,90,91), thyroid (92), and urethra (93), we also examined whether hormones could function as Tas2r activators. We found that progesterone stimulated Tas2r114 and Tas2r110.…”
Section: Substancementioning
confidence: 99%
“…urethra, thymus, thyroid gland, heart, auditory tube, airways and lung [1][2][3][4][5][6][7]. In mucosal epithelia, these chemosensory cells express one or more members of the taste receptor family 1 (Tas1R) (sweet and umami) and Tas2R (bitter) that are coupled to various G-proteins (e.g.…”
Section: Introductionmentioning
confidence: 99%